Cardiovascular risk factors in patients with aortic stenosis predict prevalence of coronary artery disease but not of aortic stenosis: an angiographic pair matched case–control study. Issue 9 (15th August 2003) - Ortlepp, J R; Schmitz, F; Bozoglu, T; Hanrath, P; Hoffmann, R
Abstract : Background: Traditional cardiovascular risk factors have been associated with aortic stenosis and coronary artery disease. As these two conditions often co-exist, the association of cardiovascular risk factors with aortic stenosis may reflect confounding. Objective: To compare the cardiovascular risk profile in patients with severe aortic stenosis undergoing elective coronary angiography with that of patients without aortic stenosis or calcification undergoing coronary angiography for suspected coronary artery disease. Methods: 523 patients referred for elective diagnostic left heart catheterisation because of severe aortic stenosis formed the case population; 3925 patients without valve disease referred for elective diagnostic left heart catheterisation formed the base control population. Of the latter, 523 were pair matched to the case population for sex, age, and prevalence of relevant coronary artery disease, forming a pair matched control population. Cardiovascular risk factors (male sex, hypertension, hypercholesterolaemia, smoking, diabetes mellitus, family history of coronary artery disease) were assessed in all the patients. Results: None of the cardiovascular risk factors was more prevalent in patients with aortic stenosis than in the base control population or in the pair matched control population. However, male sex, hypercholesterolaemia, smoking, diabetes mellitus, and a family history of coronary artery disease were significantly associated with the presence of additional coronary artery disease in patients with aortic stenosis. Conclusions: Cardiovascular risk factors are commonly present in patients with aortic stenosis. However, when compared with controls matched for age, sex, and angiographically defined coronary artery disease, no risk factor was significantly associated with the prevalence of aortic stenosis. Thus other factors are likely to be more important in the pathogenesis of aortic stenosis.